Implementation of Character Education Through Learning Models Value-Based in PPKn Subjects in Elementary Schools - Nurjannah, Vanny (International Journal of Students Education, 2024)
The implementation of character education in Elementary Schools needs to be carried out by all parties continuously. To develop character education in PPKn learning can be done by developing learning content including choosing the approach, method, model or learning strategy to be used. For this reason, the purpose of this study is to explore and describe the implementation of character education in PPKn subjects in elementary schools through a value-based learning model. This research method uses a literature review research method. The content and discussion in this study related to the implementation of character education built through this learning are values taught based on subjects such as discipline, independence, cooperation, and responsibility. In addition, learning activities that activate students through projects or problem solving will provide space for students to develop character values in PPKn learning. The results of the study show that in the implementation of character education in PPKn subjects, there are several value-based learning models that can be understood by teachers which will later become teaching materials or guidelines for teachers in realizing them in teaching and learning activities in the classroom.